Remarks on Receiving the 2001 Public Service Award - David Satcher, MD, PhD (Blackwell Synergy, 2001)
I am honored to receive the Public Service Award from the American Association of Public Health Dentistry and regret that I cannot be with you today, on the occasion of your annual meeting, to accept this recognition in person.